2020
DOI: 10.1001/jamanetworkopen.2020.0157
|View full text |Cite
|
Sign up to set email alerts
|

Association of the US Affordable Care Act With Out-of-Pocket Spending and Catastrophic Health Expenditures Among Adult Patients With Traumatic Injury

Abstract: IMPORTANCE Trauma is an expensive and unpredictable source of out-of-pocket spending for American families. The Patient Protection and Affordable Care Act (ACA) sought to improve financial protection by expanding health insurance coverage, but its association with health care spending for patients with traumatic injury remains largely unknown.OBJECTIVE To evaluate the association of ACA implementation with out-of-pocket spending, premiums, and catastrophic health expenditures (CHE) among adult patients with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 24 publications
2
55
0
Order By: Relevance
“…9,10 More directly, analyses of patient expenditures have shown an association between ACA implementation and decreased outof-pocket spending as well as risk of catastrophic health expenditures. [11][12][13][14][15] Veterans have different options for healthcare financing than the broader US population. For example, through the Veterans Health Administration (VHA), veterans with a service-related condition or meeting income eligibility thresholds may qualify for care with minimal to no cost sharing.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 More directly, analyses of patient expenditures have shown an association between ACA implementation and decreased outof-pocket spending as well as risk of catastrophic health expenditures. [11][12][13][14][15] Veterans have different options for healthcare financing than the broader US population. For example, through the Veterans Health Administration (VHA), veterans with a service-related condition or meeting income eligibility thresholds may qualify for care with minimal to no cost sharing.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous challenges facing healthcare organizations in the past few years [1][2][3] , many interventions have focused on process improvements with the objective of enhancing e ciency and e cacy to improve patient outcomes while controlling costs 4,5 . Through the years, health expenditure and nancing has increased substantially in developed countries such as the United States (US) and Canada [6][7][8][9] . In 2019, Canada spent 10.8% of its gross domestic product on healthcare expenses according to the Organization for Economic Cooperation and Development (OECD) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…47 Although the ACA has been much-maligned primarily for political purposes, research demonstrates that it reduces out-of-pocket expenses for health care dramaticallyparticularly for lower-income individuals. 48 Consequent to this research coupled with a divisive lack of trust for the current administration, 49 a recent Kaiser Family Foundation poll predictably indicated that a clear majority of Americans are now in favor of the ACA. 50 Perhaps more significant is the poll's finding that 72% believe that it is "very important" to guard against the prohibition of the ACA's clause that prevents health insurers from denying coverage for people with pre-existing conditions.…”
mentioning
confidence: 99%